Enhancing Student Character in History Education Through the Integration of Local Wisdom: The Case of the Tepuk Tepung Tawar Tradition - Herdin, Yulia; Miftahuddin, Miftahuddin; Yuliantri, Rhoma Dwi; Fikri, Asyrul (AL-ISHLAH: Jurnal Pendidikan, 2024)
Character education often overlooks the integration of local wisdom, despite its potential to significantly influence students' moral and ethical development. This study investigates the impact of incorporating the Tepuk Tepung Tawar tradition’s local wisdom values on students' character development. The research method used is an experimental method with a one group pretest-posttest design. The subjects in this research consisted of 40 students taken using a saturated sampling technique. This study's data collecting procedures included interviews and test results. The data analysis technique for this research uses the paired t-test and the N-Gain test. The results showed that there was a significant difference in student character building before and after the application of the local wisdom values of Tepung Tawar, with a significance value of less than 0.05. The N-Gain Test results showed a score of 70%, indicating an increase in student character scores after the application of the local wisdom values of Tepung Tawar. Therefore, improving student character can be done by teachers integrating local wisdom values to students in history learning.